WAREHOUSE ANALYSIS USING 5S AND ABC CLASSIFICATION METHOD ON CV. KARYA JAYA - Hanggara, Fuad Dwi (SITEKIN: Jurnal Sains, Teknologi dan Industri, 2024)
Storage room or warehouse is one of the facilities available in every company to facilitate its operations. The warehouse which is a place to store inventory of goods before the goods are issued has several activities. Due to the space that is too wide and the workers' lack of attention to the arrangement of goods on the storage rack, CV. Karya Jaya were disorganized or untidy. The arrangement of items that are still untidy makes the warehouse look ineffective and inefficient. The method used is 5S (Seiri,Seiton, Seiso, Seiketsu,Shitsuke) and ABC classification. The purpose of conducting research is to determine the arrangement of the warehouse area so that the goods look neat and effective, then ABC classification is carried out so that the categorization of goods becomes neater and in accordance with the classification so that it can make it easier for workers to search for goods in the warehouse. After doing the research, the results were Seiri 75% (quite effective), Seiton 50% (less effective), Seiso 25% (ineffective), Seiketsu 0% (very ineffective), and Shitsuke 100% (effective). There are 3 class categories, namely class A (11 items), class B (16 items), class C (27 items), proposed improvements by providing 3 shelves with the code for each product class A yellow with a high frequency of demand, class B green with medium request frequency, class C is blue with low request frequency.